Global burden and trend of substance use disorders, self-harm, and interpersonal violence from 1990 to 2021, with projection to 2040 - Jia An; Qiang Wang; Zihao Bai; Xueying Du; Di Yu; Xuming Mo (BMC Public Health)
Abstract Background Alcohol use disorders (AUD), drug use disorders (DUD), interpersonal violence, and self-harm are a major public health concern globally, with high rates of disability, morbidity, and mortality associated with this. This study aims to estimate the disease burden, trends, projections, and disparities of AUD, DUD, interpersonal violence, and self-harm among all ages and sexes from 1990 to 2021. Methods This study is a secondary analysis utilizing data from the Global Burden of Disease (GBD) 2021 in 204 countries and territories. The incidence, deaths, and disability-adjusted life years (DALYs), projection, and the inequality were estimated for AUD, DUD, interpersonal violence, and self-harm among all age and sex. Results In 2021, there were 55.78 (46.56–64.31) million new cases of AUD, 13.61 (11.63–15.67) million new cases of DUD, 29.40 (26.17–32.65) million new cases of interpersonal violence, 5.49 (4.6–6.5) million new cases of self-harm globally. By 2040, AUD is forecasted to be 51.98 (29-74.97) million, DUD will be 13.81 (9.23–18.39) million, 36.01 (15.25–56.78) million for interpersonal violence, and 10.55 (3.16–17.94) million for self-harm. In terms of gender and age distribution, males had higher incidence, mortality, and DALYs for AUD, DUD, and interpersonal violence compared to females. Females had higher incidence of self-harm, while males had higher mortality. By age group, individuals aged 15–49 bore the highest burden of DUD, interpersonal violence, and self-harm, while those aged 50–74 had the highest burden of AUD. The burden of these conditions is closely related to the socio-demographic index (SDI). High- and middle-high SDI regions had a heavier burden of AUD, DUD, and self-harm, while low- and middle-low SDI regions had a heavier burden of interpersonal violence. Additionally, from 1990 to 2021, health inequalities for AUD and self-harm decreased, while those for DUD and interpersonal violence increased. Conclusions From 1990 to 2021, the disease burden of AUD, DUD, interpersonal violence, and self-harm exhibited specific patterns across different genders, age groups, and regions. Multilevel interventions should be initiated, with a focus on reducing inequalities through resource allocation and policy support.